Persepsi Masyarakat Terhadap Ban Bridgestone - Widyaningrum, Retno (Universitas Prof. Dr. Moestopo (Beragama), 2014)
This research is aimed to know the perception of people towards Bridgestone tire. The type of research is quantitativewith survey method. The population is people who work, age 33-35 lives in Rawamangun, Pulogadung District,East Jakarta. The sample used is 45 with simple random sampling technique.Literatures in this research are studies about, communication, marketing and perception with the SOR theory asframe of mind. Data is gathered by questionnaire which used Likert scale. Analysis technique used to know theaverage perception is mean.The result of this research is that people perception towards Bridgestone tire is good (mean=3,84)